Do remote learning tools reduce learning loss during school closure? Experience from Central Asia and the Caucasus during the COVID-19 pandemic - Wataru Kodama; Peter J. Morgan; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2024)
School closures have a negative impact on children's educational outcomes. During the COVID-19 pandemic, Central Asia and the Caucasus introduced online classes and TV programs with a view to preventing learning loss. Based on a household survey in nine countries (Afghanistan, Azerbaijan, Georgia, Kazakhstan, the Kyrgyz Republic, Mongolia, Pakistan, Tajikistan, and Uzbekistan), this is one of the first regional studies to document learning loss and the efficacy of remote learning tools in Central Asia and the Caucasus. Some 79% of households felt that their children's learning progress was slower than in in-person schooling, including 39% who perceived either "very little progress" or "no progress." Our econometric analysis finds that online classes reduced perceived learning loss during school closures, but this does not hold for TV programs. In addition, traditional paper lessons were also effective in reducing perceived learning loss but only for shorter school closure durations. The usage of online classes is strongly correlated with household income and location (urban vs. rural) as well as internet connectivity. Combined usage of TV programs and paper lessons may be an effective alternative to online lessons during longer closure periods.
Keywords: I20; I21; I25; 330; remote learning; learning loss; online class; COVID-19 pandemic; Central Asia